ETHICS IN RESEARCH AND CLINICAL PRACTICE: A COMPLEX PAIRING: ÉTICA EN LA INVESTIGACIÓN Y LA PRÁCTICA CLÍNICA: UN BINOMIO COMPLEJO - Córdova Aguilar, Alberto (2019)
Health research is vital for the advancement of science and development in a country. However, researching with ethics in daily clinical practice is a slow process. Several factors play a critical role at the beginning of any investigation: the workplace, the right time, the resources with which it is counted, the number of study subjects that could be involved and even the socio familiar environment of the researcher. All these factors are directly or indirectly related to ethical problems between the doctor researcher and the patient or research subject; even more in countries like Peru, where the low educational level of the population increases a certain position of power of the doctor. Likewise, the appearance of new areas in Medicine such as palliative care, assisted human reproduction, gene therapy and tissue engineering make this pairing even more complex.